Working Ethically in Finance : Clarifying Our Vocation. - Asher, Anthony; Asher, Anthony (New York : Business Expert Press, 2015)
" a must read for those wanting to craft a vocation in finance." -- Adrian Gore, CEO, Discovery Group; " no better book for a student or practitioner who wants more than is usually on offer in finance courses in our universities." -- Paul Oslington, Professor of Economics and Dean of Business, Alphacrucis College, Sydney. To develop a vocation we ask: what do I want to be remembered for? This involves aspiring to personal integrity and a life well lived. Those working in the financial sector fulfill vocations by finding ways to serve social purposes, to allocate resources efficiently and to provide financial security-while remembering the needy. This means contributing to institutions, where people can flourish personally and create appropriate products and services. The ethics of those working on finding their vocation do not flow from rules and obligations, but from a personal commitment to seeking what is good. This life is based on the fundamental personal virtue, integrity. This book is written for those who aspire to the cultivation of the personal virtues of wisdom, self-control, courage, and justice.
Cover -- Working Ethically in Finance: Clarifying Our Vocation -- Contents -- List of Figures and Tables -- PART 1: Preliminaries -- CHAPTER 1: Vocation and Virtues -- CHAPTER 2: What is Not Covered -- CHAPTER 3: An Overview of the Finance Sector -- PART 2: Clarifying Justice -- CHAPTER 4: My Personal Experience -- CHAPTER 5: A Model of Justice -- CHAPTER 6: Injustice in Finance and Economics -- PART 3: The Purpose of Financial Services -- CHAPTER 7: Investment Management -- CHAPTER 8: Insurance and Pensions -- CHAPTER 9: Banking -- CHAPTER 10: Regulation -- CHAPTER 11: The Poor -- PART 4: Preparing Yourself: Finding a Vocation -- CHAPTER 12: Passions and Virtues -- CHAPTER 13: Developing Our Strengths -- CHAPTER 14: Serving Society's Needs -- Conclusion -- Reflection Exercise -- Bibliography -- Index -- Ad Page -- Cover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Finance--Moral and ethical aspects; Electronic books